Inorganic Nanozymes: Prospects for Disease Treatments and Detection Applications - Wang, Peng; Min, Dongyu; Chen, Guoyou; Li, Minghui; Tong, Liquan; Cao, Yonggang (Frontiers in Chemistry, 2021)
Abstract: In recent years, with the development of nanomaterials, a slice of nanomaterials has been demonstrated to possess high catalytic activity similar to natural enzymes and counter the dilemmas including easy inactivation and low yield natural of enzymes, which are labeled as nanozymes. The catalytic activity of nanozymes could be easily regulated by size, structure, surface modification and other factors. In comparison with natural enzymes, nanozymes featured with a more stable structure, economical preparation and preservation, diversity of functions and adjustable catalytic activity, thus becoming the potentially ideal substitute for natural enzymes. Generally, the are mainly three types containing metal oxide nanozymes, noble metal nanozymes and carbon-based nanozymes, owing various applications in biomedical, energy and environmental fields. In this review, to summarize the recent representative applications of nanozymes, and potentially explore the scientific problems in this field meanwhile, we are going to discuss the catalytic mechanisms of diverse nanozymes, with the emphasis on their applications in the fields of tumor therapy, anti-inflammatory and biosensing, hoping to help and guide the future development of nanozyme.